Content Validity Analysis of a Virtual Reality Based Two-Tier Multiple Choice Assessment Instrument with Ethnochemistry to Early Detect Misconceptions in Reaction Rate Topics - Arin Ika Ningtyas; Sri Yamtinah; Sulistyo Saputro; Ari Syahidul Shidiq; Sudarmin; Sri Rahayu (Postgraduate, University of Mataram, 2025)
This study aimed to develop a detection instrument for reaction rate misconceptions in prospective chemistry teachers. A Two-Tier Multiple Choice (TTMC) test with ethnochemistry content and a virtual reality (VR) storyboard were designed as assessment tools. The research followed the ADDIE model within a research and development framework. Content validity was evaluated by material and media experts through a Focus Group Discussion (FGD), with 10 TTMC questions assessed for content, language, and presentation using the Aiken formula on a 1-4 rating scale. The TTMC instrument demonstrated strong content validity, with Aiken values ranging from 0.81 to 1.00. The VR storyboard also showed content validity, with Aiken values between 0.76 and 1.00, which is above the minimum acceptable limit. These results indicate that the TTMC test and VR storyboard are valid tools for detecting misconceptions in reaction rate material, offering valuable insights for chemistry education, particularly in teacher training programs.